2007
DOI: 10.2215/cjn.03361006
|View full text |Cite
|
Sign up to set email alerts
|

North East Italian Prospective Hospital Renal Outcome Survey on Acute Kidney Injury (NEiPHROS-AKI)

Abstract: Acute kidney injury (AKI) in the intensive care unit (ICU) is associated with an enhanced mortality. The Acute Dialysis Quality Initiative group has proposed the RIFLE (Risk-Injury-Failure-Loss-ESRD) classification to standardize the approach to AKI. This study was performed to estimate the AKI incidence in ICU patients in northeastern Italy and describe clinical characteristics and outcomes of patients with AKI on the basis of their RIFLE class. A prospective multicenter observational study was performed of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
165
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(188 citation statements)
references
References 24 publications
20
165
2
1
Order By: Relevance
“…Those staged with SCr criteria have poorer outcomes compared with UO criteria (3,6,17,22), but there remains a lack of studies calibrating UO against SCr criteria (23). Using hourly observations of UO and exact AKIN criteria, we found that the UO criterion was a specific but not sensitive diagnostic test for AKI compared with SCr.…”
Section: Calibration Of Uo Criteria Relative To Scr and Its Associatimentioning
confidence: 89%
See 1 more Smart Citation
“…Those staged with SCr criteria have poorer outcomes compared with UO criteria (3,6,17,22), but there remains a lack of studies calibrating UO against SCr criteria (23). Using hourly observations of UO and exact AKIN criteria, we found that the UO criterion was a specific but not sensitive diagnostic test for AKI compared with SCr.…”
Section: Calibration Of Uo Criteria Relative To Scr and Its Associatimentioning
confidence: 89%
“…Although utilized in previous studies (3)(4)(5)(6)(7), only recently has the clinical validity of this assumption been questioned (8) and shown to result in significant bi-directional misclassification (6).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they recommended that an estimated baseline creatinine be calculated using the Modification of Diet in Renal Disease (MDRD) formula (11) with an assumed GFR for all patients between 75 and 100 ml/min. As a tool for post hoc analysis in research studies, this back-calculation method has become widespread, with most studies adopting 75 ml/min (5,8,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A few epidemiologic studies have used an estimated baseline for all of their patients (e.g., those using the Australian and New Zealand Intensive Care Society database (5,(12)(13)(14)), whereas in other studies the proportion of patients for whom a baseline is estimated by back-calculation is as low as 7% (19).…”
mentioning
confidence: 99%
“…Our results match with those of Coca et al 18 (26.6%) in American and Medve and Gondos 19 (24.4%) in Hungarian population. A much lower frequency of 10.8% has been reported by Cruz et al 20 among American population. While Lin et al 11 reported extremely high frequency of 78% among same population.…”
Section: Discussionmentioning
confidence: 67%